2023
DOI: 10.1152/ajprenal.00239.2022
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of lysyl oxidase in the pathogenesis of arterial stiffness in chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) are at increased risk for adverse cardiovascular events. CKD is associated with increases in arterial stiffness while improvements of arterial stiffness, correlates with better survival. However, arterial stiffness is increased early in CKD suggesting there might be additional factors, unique to kidney disease, that increase arterial stiffness. Lysyl Oxidase (LOX) is a key mediator of collagen cross-linking and matrix remodeling. LOX is predominantly expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Chronic kidney disease may also impair collagen cross-linking and matrix remodeling. In this context, lysyl oxidase has recently been proposed by Sharma et al, as a cofactor for the development of increased arterial stiffness in mice with early impaired kidney function [ 66 ]. Authors demonstrated that mice treated with lysyl oxidase inhibitors showed a decrease in cross-linked collagens and PWV compared to vehicle treatment.…”
Section: Clinical Risk Factor For Arterial Stiffnessmentioning
confidence: 99%
“…Chronic kidney disease may also impair collagen cross-linking and matrix remodeling. In this context, lysyl oxidase has recently been proposed by Sharma et al, as a cofactor for the development of increased arterial stiffness in mice with early impaired kidney function [ 66 ]. Authors demonstrated that mice treated with lysyl oxidase inhibitors showed a decrease in cross-linked collagens and PWV compared to vehicle treatment.…”
Section: Clinical Risk Factor For Arterial Stiffnessmentioning
confidence: 99%